New records and description of fifty-four new species of aquatic beetles in the genus Hydraena Kugelann from South America (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2011)
The South American species of the water beetle genus Hydraena Kugelann, 1794, are revised, based on the study and databasing of 2,418 specimens. New collection records are provided for 14 previously described species, and 54 new species are described. The South American fauna now comprises 82 species, only three of which are also known to be present outside of South America. Two new species groups are described, and several new species complexes are diagnosed. A neotype is designated for Hydraena paraguayensis Janssens. High resolution digital images of the holotypes of new species are presented, asare images of the primary types of 18 previously described species (online versions in color). Geographic distributions of all South American Hydraena are mapped. Male genitalia, representative female terminal abdominal segments and representative spermathecae are illustrated. New species of Hydraena are: H. altiphila (Venezuela, Rio Milla at Merida Zoo); H. amazonica (Peru, Iquitos); H. ampla (Ecuador, Quevedo, 66 km E); H. atroscintilla (Ecuador, Nono, 15.1 km NW); H. beniensis (Bolivia, 40 km E San Borja, Estacion Biologica Beni, Palm Camp at Rio Curiraba); H. boliviana (Bolivia, 40 km E San Borja, Estacion Biologica Beni, Palm Camp at Rio Curiraba); H. buscintilla (Suriname, Sipaliwini District, Camp 3, Wehepai); H. challeti (Colombia, 8.2 km NE Guarne on Hwy to Bogota); H. cherylbarrae (Venezuela, Puerto Ayacucho (40 km S), El Tobogan, Cano Coromoto); H. clinodorsa (Bolivia, Yungas Val.); H. clystera (Bolivia, Chulumani); H. cochabamba (Bolivia, Cochabamba, 105 km E Yungas, nr. Rio Carmen Mayu (Cochabamba Villa Tunari Rd.); H. concepcionica (Paraguay, Est. San Luis); H. cordispina (Peru, Parque Manu, Pakitza, Trocha Dos, c.53); H. curvosa (Brazil, Para, Rio Xingu Camp, Altamira (ca 60 km S), 1st jungle stream on trail 4); H. d-concava (Peru, Quita Calzone Rd., at km 164); H. dariensis (Colombia, Rio Atrato, Sautata); H. diffusa (Paraguay, Est. San Luis); H. duohamata (Venezuela, Cerro de la Neblina, 1.5 km S Basecamp); H. ecuadormica (Ecuador, Quevedo); H. fasciola (Ecuador, oil production platform "Villano B"); H. flagella (Paraguay, Mbocayaty, Arroyo Gervasio); H. hintoni (Brazil, Porto Velho); H. kellymilleri (Venezuela, just S. of Communidad Porvenir); H. lilianae (Argentina, Punta Lara); H. loripes (Venezuela, Stream along Rio Sipapo, S. Communidad Cano Gato); H. manabica (Ecuador, 38 km E. of Portoviejo); H. mauriciogarciai (Venezuela, Perija National Park, Tukuko, Rio Manantial); H. mintrita (Venezuela, stream nr. San Antonio); H. multiloba (Bolivia, 40 km E. San Borja, Estacion Biologica Beni, Palm Camp at Rio Curiraba); H. multispina (Peru, Quita Calzone, at km 164); H. nanoscintilla (Brazil, Cuiabá, 66 km E Serra, MT); H. neblina (Venezuela, Cerro de la Neblina); H. novacula (Peru, Buenos Aires, at km 132); H. pantanalensis (Brazil, Rio Bento Gomes (Pantanal); H. Quelle, Quellbach, Campo Allegre, II); H. peckorum (Argentina, 17 km N La Caldera, Alto de la Sierra); H. pedroaguilerai (Ecuador, Puyo, Santa Clara, Rio Llaudio Chico); H. propria (Ecuador, Paquisha, 20 km SE); H. punctilata (Brazil, Est. [Estirao] Do Ecuador); H. reverberata (Venezuela, Puerto Ayacucho (40 km S.), at Tobogan); H. scintillamima (Peru, Celendin area); H. scintillapicta (Suriname, Sipaliwini District, Camp 3, Wehepai; 2010 CI-RAP Survey); H. scintillarca (Peru, Celendin area); H. shorti (Venezuela, Perija National Park, Tukuko, Rio Manantial); H. spatula (Venezuela, NW Humocaro Bajo); H. steineri (Bolivia, 40 km E. San Borja, Estacion Biologica Beni, Palm Camp at Rio Curiraba); H. stellula (Ecuador, Santo Domingo, 79.6 km E); H. takutu (Guyana, Takutu Mountains); H. tobogan (Venezuela, Puerto Ayacucho (40 km S), at Tobogan); H. tridigita (Peru, Celendin area); H. umbolenta (Paraguay, Rio Tebicuarymi); H. unita (Brazil, Rio Bento Gomes, Pantanal); H. venezuela (Venezuela, Los Pijiguaos); H. xingu (Brazil, Rio Xingu Camp, Altamira, ca 60 km S).